Research on the Influence of the Key Stratum Position on the Support Working Resistance during Large Mining Height Top-Coal Caving Mining. (8th April 2021) - Zhang, Baisheng; Yang, Zhiping; Ji, Chunxu; Guo, Zefeng; Li, Haoyang
Abstract : In recent years, in order to increase the coal recovery rate, the large mining height fully mechanized top-coal caving mining has been widely used because it has the advantages of both fully mechanized mining method and large mining height mining method. When this mining technology is used to exploit thick coal seam under upper goaf, the movement characteristics of the overlying strata and the bearing structure formed by the broken rock are complicated, which results in the abnormal pressure during mining, such as severe coal slabs and hydraulic supports being crushed. The key to solve these problems is to study the movement law and the structural evolution characteristics of the overlying strata during large mining height fully mechanized top-coal caving mining, and the movement characteristics of the overlying strata are all determined by the layer-position of the key stratum. UDEC models with different layer-position of the key stratum are established to investigate the influence of the key stratum position on the support working resistance during large mining height top-coal caving mining. Through comprehensive research, the source of support resistance comes from under different geological conditions was analyzed, and the formula for estimating the maximum support working resistance was deduced. In addition, in order to release the severe pressure during large mining height fully mechanized top-coal caving mining, it is recommended to use hydraulic fracturing method to weaken the key stratum in situ.